Biodiversity in forestry education: what needs to change?: In: Temu, A.B.; Chamshama, S.A.O.; Kung’u, J.; Kaboggoza, J.; Chikamai, B.; Kiwia, A. (eds.) 2008. New Perspectives in Forestry Education. Peer reviewed papers presented at the First Global Workshop on Forestry Education, September 2007. ICRAF, Nairobi, K - Rudebjer, P.G.; Eyog-Matig, O.; Thomson, L. (ANAFE, 2008)
A paper presented at the First Global Workshop on Improving Forestry Education at ICRAF, Kenya in September 2007. Education on forest genetic resources has largely focused on tree breeding of plantation species and conservation ecology to protect forest biodiversity under threat, with less attention to the livelihood or landscape dimensions of forest biodiversity. Forest education curricula need to be enriched with broader views to take into account socioeconomic and policy-related dimensions of forest biodiversity, including ‘conservation through use’ in mosaic landscapes.